A systematic review comparing single-incision versus multi-incision laparoscopic surgery for inguinal hernia repair with mesh. (May 2016) - Sajid, M.S.; Khawaja, A.H.; Sayegh, M.; Baig, M.K.
Abstract: Objective: The objective of this article is to evaluate whether the surgical outcomes differ between single incision laparoscopic surgery (SILS) versus multi-incision laparoscopic surgery (MILS) for the repair of inguinal hernia. Methods: A systematic review of the literature on published studies reporting the surgical outcomes following SILS versus MILS for inguinal hernia repair was undertaken using the principles of meta-analysis. Results: Fifteen comparative studies on 1651 patients evaluating the surgical outcomes in patients undergoing SILS versus MILS for inguinal hernia repair were systematically analysed. The post-operative recovery time was significantly quicker [odds ratio, −0.35 (CI, −0.57 – 0.14), p = 0.001] following SILS compared to MILS procedure. However, the statistical equivalence was seen in outcomes of length of hospital stay, operative time both for unilateral and bilateral hernias, post-operative pain score, one-week pain score, hernia recurrence [odds ratio, 1.24 (CI, 0.47–3.23), p = 0.66], conversion [odds ratio, 1.07 (CI, 0.37–3.12), p = 0.90], and post-operative complications [odds ratio, 0.95 (CI, 0.66–1.36, p = 0.78] between two approaches. The sub-group analysis of four included randomized, controlled trials showed similarities between outcomes following SILS and MILS except slightly higher postoperative pain score in MILS group. Conclusions: Both SILS and MILS approaches of inguinal hernia repair are feasible, safe and can be offered to patients depending upon the availability of expertise and resources. Highlights: Single incision laparoscopic inguinal (SILS) hernia repair has several advantages such as better cosmesis and reduced pain score and analgesics requirements. This study presents meta-analysis of fifteen comparative studies on 1651 patients undergoing SILS versus conventional multi-incision laparoscopic (MILS) inguinal hernia repair. The recovery time was significantly quicker in SILS compared to MILS group However, the statistical equivalence was seen in outcomes of length of hospital stay, operative time both for unilateral and bilateral hernias, post-operative pain score, one-week pain score, recurrence, conversion [odds ratio, and post-operative complications. Both SILS and MILS approaches of laparoscopic inguinal hernia repair are feasible, safe and can be offered to patients depending upon the availability of expertise and resources.